Extensive Genetic Differentiation between Homomorphic Sex Chromosomes in the Mosquito Vector, Aedes aegypti. (1st September 2017) - Fontaine, Albin; Filipović, Igor; Fansiri, Thanyalak; Hoffmann, Ary A.; Cheng, Changde; Kirkpatrick, Mark; Rašić, Gordana; Lambrechts, Louis
Abstract: Mechanisms and evolutionary dynamics of sex-determination systems are of particular interest in insect vectors of human pathogens like mosquitoes because novel control strategies aim to convert pathogen-transmitting females into nonbiting males, or rely on accurate sexing for the release of sterile males. In Aedes aegypti, the main vector of dengue and Zika viruses, sex determination is governed by a dominant male-determining locus, previously thought to reside within a small, nonrecombining, sex-determining region (SDR) of an otherwise homomorphic sex chromosome. Here, we provide evidence that sex chromosomes in Ae. aegypti are genetically differentiated between males and females over a region much larger than the SDR. Our linkage mapping intercrosses failed to detect recombination between X and Y chromosomes over a 123-Mbp region (40% of their physical length) containing the SDR. This region of reduced male recombination overlapped with a smaller 63-Mbp region (20% of the physical length of the sex chromosomes) displaying high male–female genetic differentiation in unrelated wild populations from Brazil and Australia and in a reference laboratory strain originating from Africa. In addition, the sex-differentiated genomic region was associated with a significant excess of male-to-female heterozygosity and contained a small cluster of loci consistent with Y-specific null alleles. We demonstrate that genetic differentiation between sex chromosomes is sufficient to assign individuals to their correct sex with high accuracy. We also show how data on allele frequency differences between sexes can be used to estimate linkage disequilibrium between loci and the sex-determining locus. Our discovery of large-scale genetic differentiation between sex chromosomes in Ae. aegypti lays a new foundation for mapping and population genomic studies, as well as for mosquito control strategies targeting the sex-determination pathway.